Size growth and age of two congeneric archer fishes (Toxotes jaculatrix pallas, 1767 and Toxotes chatareus Hamilton, 1822) inhabiting Malaysian coastal waters - K.D. Simon,; A.G. Mazlan,; A. Samat,; C.C. Zaidi, (Universiti Kebangsaan Malaysia, 2010)
The size, growth and age of two congeneric archer fishes Toxotes jaculatrix and Toxotes chatareus collected from Johor coastal waters, Malaysia was studied. The standard length (SL) and body weight (BW) ranges of the two species caught in the study area were 7-12.2 cm SL (9.35±0.19 cm), 11-55 g BW (27.04±1.62 g) and 8-12.2 cm SL (9.88±0.17cm), 15.12-54g BW (30.52±1.72 g), respectively. The ratio of male and female specimens of T. jaculatrix and T. chatareus were 70%, 30% and 68.6%, 31.4%, respectively. The estimated von Bertalanffy growth parameters were L∞ = 12.78 cm, 13.59 cm and K = 1.46 year-1, 1.53 year-1 with a growth performance index of Ø’ = 5.48 and 5.64 in both species, respectively. In order to determine the age, the technique of reading and interpretation of the daily growth increments/rings in the sagittae otoliths and scales were applied. Daily growth increments and annulus of scales counts confirmed that the ages of the samples for both species were typically less than one year (<1) and the remnant samples were between one and two years. The similarity between scale and otolith age determination was identical and dissimilarity was observed only in few samples of both species.